Multiple unfolded protein response pathways cooperate to link cytosolic dsDNA release to stimulator of interferon gene activation - Hu, Tiancheng; Liu, Yiping; Fleck, Jeremy; King, Cason; Schalk, Elaine; Zhang, Zhenyu; Mehle, Andrew; Smith, Judith A. (Frontiers in Immunology, 2024)
The double-stranded DNA (dsDNA) sensor STING has been increasingly implicated in responses to "sterile" endogenous threats and pathogens without nominal DNA or cyclic dinucleotide stimuli. Previous work showed an endoplasmic reticulum (ER) stress response, known as the unfolded protein response (UPR), activates STING. Herein, we sought to determine if ER stress generated a STING ligand, and to identify the UPR pathways involved.or oxygen glucose deprivation required both STING and the dsDNA-sensing cyclic GMP-AMP synthase (cGAS). Furthermore, TPG increased cytosolic mitochondrial DNA, and immunofluorescence visualized dsDNA punctae in murine and human cells, providing a cGAS stimulus. N-acetylcysteine decreased IFN- induction by TPG, implicating reactive oxygen species (ROS). However, mitoTEMPO, a mitochondrial oxidative stress inhibitor did not impact TPG-induced IFN. On the other hand, inhibiting the inositol requiring enzyme 1 (IRE1) ER stress sensor and its target transcription factor XBP1 decreased the generation of cytosolic dsDNA. iNOS upregulation was XBP1-dependent, and an iNOS inhibitor decreased cytosolic dsDNA and IFN-, implicating ROS downstream of the IRE1-XBP1 pathway. Inhibition of the PKR-like ER kinase (PERK) pathway also attenuated cytoplasmic dsDNA release. The PERKregulated apoptotic factor Bim was required for both dsDNA release and IFN- mRNA induction. Finally, XBP1 and PERK pathways contributed to cytosolic dsDNA release and IFNinduction by the RNA virus, Vesicular Stomatitis Virus (VSV). Together, our findings suggest that ER stressors, including viral pathogens without nominal STING or cGAS ligands such as RNA viruses, trigger multiple canonical UPR pathways that cooperate to activate STING and downstream IFN- via mitochondrial dsDNA release.